Martabat Tembung Wali of Sunan Gunung Jati: As the value of religious humanism for the people of Cirebon - Pradita, Linda E. (HTS teologiese studies, 2020)
This study discusses the teachings of Sunan Gunung Jati as the value of religious humanism in education and history for the people of Cirebon. The teachings of Sunan Gunung Jati are still tightly grasped by the people of Cirebon from ancient times to the present, namely martabat tembung wali because they contain moral teachings and noble cultural values. The teachings of Sunan Gunung Jati have the concept of religious humanism as a form of history. The concept of religious humanism has implications for the educational process, with an orientation to developing human aspects. The purpose of this study is to explore the values of life reflected in the teachings of Sunan Gunung Jati’s life as the value of religious humanism in education and history for the people of Cirebon. This research uses an anthropolinguistic theoretical framework to examine the value of religious humanism in education and history for the people of Cirebon. This study uses a qualitative research paradigm. The results showed that the teachings of Sunan Gunung Jati contained the value of life in social rules. Sunan Gunung Jati has relevance to the process of human development. Humans have a personal side that continues to grow in line with the social side. Human development is also surrounded by spiritual components as a form of emotional intelligence.Contribution: This article contributes to the objective of HTS Teologiese Studies/Theological Studies to investigate the history of religions, as well as phenomenology, psychology, philosophy and sociology of religions.